Liver Abscess as a Rare Complication of Typhoid Fever in a Young Adult: A Case Report - Pratama, Gede Made Cahya Trisna; Putra, I Komang Wisuda Dwija (Jurnal Locus Penelitian dan Pengabdian, 2026)
Typhoid fever, caused by Salmonella typhi, remains a significant endemic infection in developing countries. While its gastrointestinal and systemic symptoms are well known, liver abscess as a complication is exceedingly rare. This case report highlights the clinical significance of recognizing atypical presentations, particularly in resource-limited settings with common delayed diagnosis. The condition arises from hematogenous spread of Salmonella typhi in delayed or untreated cases, leading to localized hepatic infection and abscess formation. This descriptive case report documents this rare complication. A 19-year-old male presented with persistent high-grade fever, malaise, headache, and right upper quadrant abdominal pain, plus a history of hematochezia. Examination revealed fever, anemic conjunctivae, and hepatomegaly. Labs showed leukocytosis with neutrophilia, microcytic anemia, elevated liver enzymes, and positive fecal occult blood. The TUBEX TF test was reactive for IgM against Salmonella typhi. Abdominal ultrasonography and contrast-enhanced CT confirmed a solitary liver abscess. Initial ceftriaxone monotherapy yielded limited response; significant improvement followed added intravenous metronidazole. A 19-year-old male presented with persistent high-grade fever, malaise, headache, and right upper quadrant abdominal pain, plus a history of hematochezia. Examination revealed fever, anemic conjunctivae, and hepatomegaly. Labs showed leukocytosis with neutrophilia, microcytic anemia, elevated liver enzymes, and positive fecal occult blood. The TUBEX TF test was reactive for IgM against Salmonella typhi. Abdominal ultrasonography and contrast-enhanced CT confirmed a solitary liver abscess. Initial ceftriaxone monotherapy yielded limited response; significant improvement followed added intravenous metronidazole.